DESIGN OF AN ALIGNER AND QUICK HITCH FOR THE TRACTOR DRAWBAR - de Rezende, Milena Luiza Lima; do Vale, Welington Gonzaga; Pereira, Diego Andrade; Andrade, Valfran José Santos; Enes, Adilson Machado; Santos, Antônio Pereira; do Vale, Patricia de Azevedo Castelo Branco (Editora Impacto Científico, 2025)
Agricultural mechanization has been essential in promoting greater efficiency, safety, and productivity in the field. However, operations such as hitching and unhitching implements to the tractor drawbar are still performed manually on many farms, leading to operational risks and time losses. This work proposes the conceptual development of a quick hitch device with an automated aligner for agricultural tractors, based on a design methodology that allows revisions and iterations with previous stages for corrections and improvements when necessary, in compliance with Regulatory Standard NR 31. Technologies such as directional valves, electro-hydraulic, electropneumatic, and electric actuators were explored with the goal of eliminating the need for manual operator intervention. The results indicate a feasible solution adaptable to different tractor models, which can significantly improve ergonomics, safety, and the standardization of agricultural operations. The study also highlights the importance of innovation in the field through automation and the use of structured product development methodologies.DOI: https://doi.org/10.56238/edimpacto2025.071-001